2012
DOI: 10.1371/journal.pone.0053188
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects and Antivenom Dosing in Brown Snake (Pseudonaja spp.) Envenoming — Australian Snakebite Project (ASP-14)

Abstract: BackgroundSnakebite is a global health issue and treatment with antivenom continues to be problematic. Brown snakes (genus Pseudonaja) are the most medically important group of Australian snakes and there is controversy over the dose of brown snake antivenom. We aimed to investigate the clinical and laboratory features of definite brown snake (Pseudonaja spp.) envenoming, and determine the dose of antivenom required.Methods and FindingThis was a prospective observational study of definite brown snake envenomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(186 citation statements)
references
References 29 publications
5
175
1
2
Order By: Relevance
“…In studies of venom concentrations in Australian elapids venom is almost never detected post-antivenom (Isbister et al, 2013a;Allen et al, 2012). In this study we analysed three rare brown snake patients where there was venom detected postantivenom which was shown also to be mainly bound venom (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In studies of venom concentrations in Australian elapids venom is almost never detected post-antivenom (Isbister et al, 2013a;Allen et al, 2012). In this study we analysed three rare brown snake patients where there was venom detected postantivenom which was shown also to be mainly bound venom (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Patients (>13 years of age) presenting with Russell's viper envenoming were included if venom was detected in the patients' serum with a Russell's viper venom specific ELISA, at least four serum samples at different time points were available for analysis and a pre-antivenom sample was available. Serial samples were also available from patients with brown snake envenoming who were recruited to the Australian snakebite project (Allen et al, 2012). All serum samples were immediately centrifuged after collection, then aliquoted and stored at À80 C until analysed.…”
Section: Patient Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, death due to 'brown snakeinduced early cardiovascular collapse' is the most common cause of death from snake envenoming in Australia (Allen et al, 2012;Currie, 2004). The early cardiovascular collapse following the injection of snake venom has been shown in a number of in vivo studies (Chaisakul et al, 2012(Chaisakul et al, , 2013, but the toxins responsible for this effect are yet to be identified and the mechanism(s) behind cardiovascular collapse remain unclear.…”
Section: Introductionmentioning
confidence: 99%